Learning Cycle 5E through Interactive Simulator to Improve Understanding of Molecular shapes and Chemistry Identity - Pitaloka, Dinda Ayu; Muntholib, Muntholib; Dasianto, Dasianto (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to improve students understanding of concepts and chemistry identity in molecular shape material through the application of the learning cycle 5E (LC 5E) model assisted by interactive digital simulator media. The research method used is classroom action research (CAR) with the Kemmis and Taggart model. The model has four stages, namely planning, action, observation, and reflection. The subjects in this study were 32 students from class X-3 SMA Brawijaya Smart School in the 2024/2025 academic year. The data obtained were analyzed descriptively. Based on the results of the study, it is known that in cycle I, the application of LC 5E assisted by interactive digital simulator media has not been able to improve understanding of molecular shapes and the percentage increase in students' chemistry identity is low. Therefore, improvements were made in cycle II referring to the results of the reflection, there was an increase in concept understanding from 68% to 82% with classical completeness reaching 81%. In addition, the n-gain value of 71.8% was obtained, indicating that the application of the LC 5E model assisted by interactive digital simulator media was quite effective in improving students' concept understanding on molecular shape material. There was also an increase in students' chemistry identity, especially related to the indicators of mastery experiences and verbal persuasion, 57% and 50% respectively. Thus, it can be concluded that through the application of the 5E learning cycle model assisted by interactive digital simulator media on the material of molecular shapes is effective enough to improve students' concept understanding and chemistry identity.